Возможности ПЭТ/КТ С 18F-ФДГ в диагностике и стадировании лимфом; Вопросы онкологии; Т. 65, № 1 - Чанчикова Н. Г. Наталья Геннадьевна; Дудникова Е. А. Екатерина Александровна; Карлова Е. А. Елена Анатольевна; Савельева А. С. Анастасия Сергеевна; Силкина О. А. Ольга Андреевна; Зельчан Р. В. Роман Владимирович; Синилкин И. Г. Иван Геннадьевич; Брагина О. Д. Ольга Дмитриевна; Медведева А. А. Анна Александровна; Чернов В. И. Владимир Иванович (2019, 2019)
Заглавие с экрана